State audit board and the performance of regional government-linked companies in the Republic of Indonesia - Amdanata, Donal Devi
The 1997 Asian economic crisis has resulted in the e tablishment of a National Committee on Governance (NCG) in Indonesia. One of the outcomes of the crisis was regional autonomy where each provincial government was authorized to generate income through business activities. Thus, state-owned Regional Government-Linked Companies (RGLCs) were established under the local government. Since its establishment the performanc f these profit oriented RGLCs has been a m~ concern and State Audit Board (SAB) was created to perform the external audit of the RGLCs. SAB conduct three types of audit, namely financial audit, performance audit and audits for specific purpose. The main role of SAB is to examine the state finances of RGLCs and monitor the implementation of audit recommendations. This tudy examines the effects of SAB, government programs, the board of directors' exp rtise, type of capital and government connections on the performance of RGLCs with government regulation a a mediating variable. The quantitative method using survey questionnaire was u ed to collect the data. There are 426 RGLCs in Indonesia and a total of 57 non-bank RGLCs were involved in this study after eliminating those which do not me t the election criteria. Six types of respondents were selected from each of the sampled RGLCs representing Directors, Financial Managers, Accounting Managers, Audit Committee member, Internal Supervisory Units, Financial or Accounting Supervisors and financial or accounting staff. Accounting expert state auditors, and directors of RGLCs and former directors of the RGLCs were involved in building th questionnaire. A pilot study was conduct d before the questionnaire was distributed to 342 respondents. A total of 290 (85%) of the questionnaire was returned. Howe er, only 209 (61 %) of the RGLCs as audited by SAB and answered the qu tionnaire completely. This study used SmartPLS for the data analysis. Based on multiple regression analysis the findings suggest that the audits of SAB have mixed effects on the RGLCs' performance. The financial audit does not affect performance while the compliance audits have a significant positive effect. Similarly, government regulations contribute p itively to performance whereas government connections negatively impacted the RGLCs' performance. The findings also show mixed results on the mediating role of government regulation. Although the findings of the research are mixed, thi study suggests that the AB's audits of RGLCs should be continued since the compliance audit positively contributes to the RGLCs' performance. Various government entities associated with the RGLCs and SAB should establish effective communication with RGLCs. The r gional government as the owner of the RGLCs must strive to strengthen the governance of the RGLCs. Local governments hould continue to get SAB involved in improving RGLCs' compliance to strengthen performance. Additionally, the central government and SAB should produce audit guidelines and procedures for the purpose of audit of government institutions to improve the effectiveness of the RGLCs' audit.